A new approach for fabricating germanene with Dirac electrons preserved: a first principles study. Issue 8 (8th February 2016) - Li, Ping; Cao, Juexian; Guo, Zhi-Xin
Abstract : We propose a new approach to fabricating germanene in which the Dirac electronic properties are preserved very well. Abstract : How to obtain germanene with Dirac electrons preserved is still an open challenge. Here we report a sandwich-dehydrogenation approach, i.e., to fabricate germanene through dehydrogenating germanane in a sandwiched structure. Dehydrogenation can spontaneously occur for the sandwiched structure, which overcomes the problem of amorphization in the heating dehydrogenation approach. The obtained germanene preserves the Dirac electronic properties very well. Moreover, the Fermi velocity of germanene can be efficiently manipulated through controlling the interlayer spacing between germanane and the sandwiching surfaces. Our results indicate a guideline for the fabrication of perfect two-dimensional materials.